2020
DOI: 10.1002/rcs.2043
|View full text |Cite
|
Sign up to set email alerts
|

A novel enhanced intensity‐based automatic registration: Augmented reality for visualization and localization cancer tumors

Abstract: The purpose of this study is to replace the manual process (selecting the landmarks on mesh and anchor points on the video) by Intensity‐based Automatic Registration method to reach registration accuracy and low processing time. The proposed system consists of an Enhanced Intensity‐based Automatic Registration (EIbAR) using Modified Zero Normalized Cross Correlation (MZNCC) algorithm. The proposed system was implemented on videos of breast cancer tumors. Results showed that the proposed algorithm—as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(42 reference statements)
0
2
0
Order By: Relevance
“… Correspondence: Establishing a correspondence between the input data is based on the input modalities and their available features. The three common approaches for determining the correspondence are [ 20 ]: segmentation [ 21 ], sparse features (i.e., points, edges, objects) [ 22 ], or signal intensity (i.e., MRI or US signal, radiological density) [ 23 , 24 ]. Feature-based approaches are known to be less complex in terms of computation, where the transformation matrix could be directly obtained from the correspondence of features between two modalities or by a simple algorithm (e.g., least squares [ 25 ]).…”
Section: Introductionmentioning
confidence: 99%
“… Correspondence: Establishing a correspondence between the input data is based on the input modalities and their available features. The three common approaches for determining the correspondence are [ 20 ]: segmentation [ 21 ], sparse features (i.e., points, edges, objects) [ 22 ], or signal intensity (i.e., MRI or US signal, radiological density) [ 23 , 24 ]. Feature-based approaches are known to be less complex in terms of computation, where the transformation matrix could be directly obtained from the correspondence of features between two modalities or by a simple algorithm (e.g., least squares [ 25 ]).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 For such intervention scenarios, many studies have shown the advantages of using virtual or augmented reality (AR) interfaces to improve surgical procedure's accuracy and efficiency. [20][21][22][23][24][25][26] These output interfaces enables the surgeon to visualise and focus on critical anatomy in an immersive and intuitive setting, while also increasing insight on anatomy/pathology of the disease. 18 Moreover, such a computational facility enables 'relevance-based visualisation' by enabling the display of virtual data for different phases of the procedure.…”
Section: Introductionmentioning
confidence: 99%